Effects of Different Intensities and Durations of Aerobic Exercise on Vascular Endothelial Function in Middle-Aged and Elderly People: A Meta-analysis - You, Qiuping; Yu, Laikang; Li, Gen; He, Hui; Lv, Yuanyuan (Frontiers in Physiology, 2022)
Background: Previous studies have found that aerobic exercise was more effective in improving vascular endothelial function than resistance training, high-intensity interval training (HIIT), and other types of exercise, while the effects between different intensities and durations of aerobic exercise were unclear. Therefore, we performed this meta-analysis to investigate the effects of different intensities and durations of aerobic exercise on the vascular endothelial function of middle-aged and elderly people. Methods: Databases were searched up to April 2021 for studies evaluating the influences of different intensities and durations of aerobic exercise on endothelial function assessed by flow-mediated dilation (FMD) among healthy middle-aged and elderly people. Data were pooled using random-effects models to obtain the weighted mean difference (WMD) and 95% confidence intervals (CIs). Results: A total of 9 studies involving 221 participants fulfilled the inclusion criteria. Aerobic exercise improved the overall FMD of healthy middle-aged and elderly people (WMD, 1.33 [95% CI, 0.37-2.28], P < 0.05). Specifically, vigorous-intensity exercise increased FMD significantly in healthy middle-aged and elderly people (WMD, 1.10 [95% CI, 0.27-1.93], P < 0.05), while moderate-intensity exercise had no significant association with FMD (WMD, 1.49 [95% CI, -0.62-3.60], P = 0.17). In addition, long-term (8 weeks or above) aerobic exercise increased the FMD in healthy middle-aged and elderly people (WMD, 1.63 [95% CI, 0.61-2.66], P < 0.05), while one-time acute aerobic exercise had no significant association with FMD of healthy middle-aged and elderly people (WMD, 0.89 [95% CI, -1.47-3.24], P = 0.46).Specifically, 8 weeks or above of vigorous-intensity exercise increased FMD significantly in healthy middle-aged and elderly people (WMD, 1.48 [95% CI, 1.06-1.90], P < 0.01), while 8 weeks or above of moderate aerobic exercise had no significant association with FMD (WMD, 1.49 [95% CI, -0.62-3.60], P = 0.17). Conclusion: Aerobic exercise, especially 8 weeks or above of vigorous-intensity aerobic exercise, improved the endothelial function in healthy middle-aged and elderly people.